Perineural spread evaluation of cranial nerves in nasopharyngeal carcinoma: superiority and reliability of isovolumetric MR imaging - Zheng, Dechun; Xu, Shugui; Lai, Guojing; Hu, ChunMiao; Cao, Xisheng; Feng, Meimei; Peng, Li (Frontiers in Oncology, 2024)
PurposeThe purpose of this study was to investigate the advantage of three-dimensional liver acquisition with volume acceleration-flexible (3D LAVA_Flex) for perineural spread (PNS) status of nasopharyngeal carcinoma (NPC) in comparison with two-dimensional magnetic resonance sequences.Materials and methodsSixty pathological proved NPC patients were prospective enrolled. A protocol included T2-weighted imaging with fat suppression (T2WI fs), T1-weighted imaging (T1WI) without and with contrast enhancement (T1WI ce), and 3D LAVA_Flex was applied for the recruited subject. After determining radiologic diagnostic criteria, the PNS status of cranial nerves (CNs) was carefully interpreted and recorded at the nerve level, anterior and posterior subgroup level, and individual level, respectively. Chi-square test [or McNemar-Bowker (MB) test], Fisher test, and intraclass correlation analysis were used. A P < 0.05 indicated statistical significance.ResultsPNS rates of the CNs in the advanced T3 to T4 stage subgroup were significantly different in evaluations performed with 3D LAVA_Flex, T2WI fs, T1WI, and T1WI ce at the patient level (n = 51, MB test, all P ≤ 0.031) and posterior CN level (MB test, all P ≤ 0.016). At the nerve level, 3D LAVA_Flex showed greater PNS detectability than T2WI fs, T1WI, and T1WI ce for CN V3 division (P = 0.031, 0.016, and 0.016, respectively), hypoglossal nerve (P = 0.002, 0.016, and 0.008, respectively), and external posterior CN IX–XII in carotid space (all P = 0.001), and T2WI fs and T1WI for CN IX–XI (P = 0.031, 0.001).Conclusions3D LAVA_Flex could improve both accuracy and reliability of PNS evaluation of CNs in the advanced NPC cohort and may facilitate decision making for therapeutic strategies.